Pemberdayaan Perempuan Melalui Penguatan Ketahanan Pangan: Peran Kelompok Wanita Tani (KWT) dan Penggiat PKK dalam Pengembangan Komoditas Hortikultura Berbasis Urban Farming di Desa Cemani, Grogol, Sukoharjo - Pradana, Anditya Gilang Rizky; Pranata, Muhammad Fariz Yoga; Wijayanti, Bela Tri; Nurhidayati, Febry; Adillah, Aulia; Suprihatin, Dewi Nawang; Suryadi, Didik; Hantari, Dimar; Seto, Rehino Yanu (Adi Widya : Jurnal Pengabdian Masyarakat, 2025)
Cemani Village, Grogol District, Sukoharjo, has great potential to be developed as an agrotourism destination, thanks to its fertile land and strong community support. However, the development of the agricultural sector, particularly orchard, remains limited. This community service program aims to empower women through the Farmers Women’s Group (KWT) and PKK, with focus on food security through urban farming. Activities include extension of superior seed planting, training in horticultural cultivation techniques, and distribution of seeds to the community. The program also introduces the concept of agrotourism to boost income through harvests and educational tours. The results show an increased understanding of sustainable cultivation techniques. To ensure the program's sustainability, further training, infrastructure development, and routine monitoring are required, along with collaboration between the village government, universities, and BUMDes to establish Cemani Village as a model of agrotourism destination.